Piedmont sedimentation in the headwaters of the Río Jachal and Pampa de Gualilán, Precordillera of San Juan - Suriano, J. (2009)
This paper deals with the sedimentological characteristics of piedmont deposits exposed in intramontane basins of the Precordillera. Detailed studies carried out along the upper Jáchal river and in the Gualilán area allowed identifying and characterizing six major types of piedmont accumulations: 1) talus, 2) colluvial fans dominated by gravity flows, 3) colluvial fans dominated by fluid flows, 4) collector-conoid fluvial system, 5) piedmonts dominated by channalized flows and 6) alluvial fans. The talus deposits are characterized by the dominance of clast-supported breccias (bearing minimum matrix amounts) that commonly exhibit massive bedding, planar or high angle imbricated clasts fabric. Colluvial fans dominated by gravity flows are formed by massive matrix-supported breccias with minor percentages of clast-supported breccias. On the contrary, colluvial fans dominated by fluid flows are composed of amalgamated channels infilled by both clast- and matrix-supported breccias together with intercalation of graded breccias. Accumulations of the collector-conoid fluvial systems are the most diverse in composition, including from massive matrix-supported breccias to cross-bedded conglomerates and scarce mudstones. In relation to the piedmont dominated by channalized flows, they comprise massive clast-supported breccias and less amounts of imbricated or cross-bedded ones. The alluvial fan deposits are mostly composed of cross-bedded clast-supported conglomerates, though matrix-supported conglomerates and breccias also appear as proximal deposits. Different from the previously mentioned deposits, the clast of alluvial fan accumulations shows more varied lithologic composition. The comparative analysis of the piedmonts found in the studied valleys permits to propone a conceptual model for classification of piedmont, on the basis of the extension of the basins and vertical space of accommodation.